Creation of CdTe nanoclusters in SiO 2 /Si track tamplates using two types of electrolyter - Балахаева, Р; Акилбеков, А; Даулетбекова, А; Козловский, А; Баймуханов, З; Гиниятова, Ш; Усеинов, А; Садуова, Б; Карим, К (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article presents the results of the study of CdTe nanoclusters obtained by electrochemical deposition using sulphate and chloride solutions. The SiO 2 /Si track templates were used as nanoporous templates. The a-SiO 2 /Si-n track template was obtained by irradiation with xenon ions with an energy of 200 MeV, with fluences of 10 7 –10 8 ions/cm 2 . The surface of the deposited samples was examined using a JSM 7500F scanning electron microscope. To identify the crystal structure of CdTe nanoclusters, an X-ray structural analysis was carried out to form cadmium telluride nanocrystals of the hexagonal phase (wurtzite) together with the amorphous phase. Calculations of crystallite sizes showed that after annealing of CdTe samples at a temperature of 100 ◦ C leads to changes in nanostate and an increase in the degree of crystallinity with the dominance of the amorphous phase.